Econometric analysis of income, productivity and diversification among smallholders in Brazil. (July 2018) - Herrera, Gabriel Paes; Lourival, Reinaldo; da Costa, Reginaldo Brito; Mendes, Dany Rafael Fonseca; Moreira, Tito Belchior Silva; de Abreu, Urbano Gomes Pinto; Constantino, Michel
Highlights: The paper analyses the most current available data of smallholder farming in Brazil. Identification of determinants to improve income, productivity and diversification. Cooperativeness is one of the most important factors to improve the three cases. Signs of gender inequality were found and deserves special attention. Results and updated data enable policy-makers to make more informed decisions. Abstract: Family farming plays important roles in agricultural production and the world's food security. This paper provides an econometric analysis of income, productivity and diversification of Brazilian smallholders. Using the most updated data from the Ministry of Agrarian Development (MDA) enables a more precise analysis than traditional agri-census data. The database contains approximately 4.7 million family farmers from all regions of the country. We used linear and tobit regression to untangle useful information behind these large datasets. The results demonstrated that the smallholders that are part of an agricultural cooperative or a member of a farmer's association positively affect income, productivity and diversification. The age of household heads is shown to have a non-linear relationship in the three cases, while the household head being female presented a negative effect in all regressions. Although recent technical assistance showed negative impacts on income and productivity, farmer's assistance positively affected the likelihood of a smallholder diversifying their production and, therefore, becoming less subject to price imbalances. The results support current views in the field of smallholder farming while presenting marked regional differences of a continental country, enabling policy makers to make better, more informed decisions.